Angiotensin-converting enzyme (ACE-I/D) polymorphism frequency in Brazilian soccer players - Barbosa Coelho, D.; Pimenta, .; Cruz Rosse, I.; Veneroso, C.; Pussieldi, G.; Kapes Becker, L.; Carvalho, M.-R.; Silami-Garcia, E. (Applied Physiology, Nutrition, and Metabolism, 2016)
This study aimed to analyze the angiotensin-converting enzyme (ACE-I/D) allelic and genotypic frequencies in Brazilian soccer players of different ages. The study group comprised 353 players from first-division clubs in the under (U)-14, U-15, U-17, U-20, and professional categories. The allelic and genotypic frequencies did not differ significantly in any of the categories between the group of players and the control group. This was the first study of ACE-I/D polymorphism in Brazilian soccer players.